PENGARUH IKLAN TELEVISI DAN ENDORSER VALENTINO ROSSI TERHADAP BRAND AWARENESS DAN KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA NMAX DI PEKANBARU - Alvi, Alwie Furwanti; Aida, Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of Television Advertising and Endorser Valentino Rossi on Brand Awareness and Purchase Decisions of Yamaha NMAX Motorbikes in Pekanbaru. The population in this study were all Yamaha N-Max motorbike users in Pekanbaru, amounting to 937 in 2019. This study used a sample of 109 respondents using the Slovin formula. The types of data used are primary and secondary data, while data collection techniques use questionnaires and literature study. Data analysis using path analysis (path analysis). The results showed that television advertising and endorser Valentino Rossi partially had a significant effect on Brand Awareness, Television Advertising and Endoirser Valentino Rossi partially had a significant effect on purchasing decisions, Brand Awareness had a significant effect on purchasing decisions. Television Advertising and Endorser Valentino Rossi have a significant effect on purchasing decisions through Brand AwarenessKeywords: Television Advertising, Endorser Brand Awareness, Purchasing Decisions